MODERASI BERAGAMA: PENANAMAN PADA LEMBAGA PENDIDIKAN FORMAL DAN NONFORMAL - M. Kholis Amrullah; Lutfiatuz Zahro'; M. Irfan Islamy (Nizham Journal of Islamic Studies, 2021)
Educational institutions as part of social life are the main sector in advancing the life of the nation. This role is a great opportunity to instill good reforms in the progress of people's thinking. Religious moderation is the main subject in the discussion in this article to review its existence in formal and non-formal educational institutions. The results of the discussion show that the highest formal educational institution, namely universities, is the main laboratory in developing and implementing religious moderation. The results of this development are then given to universities themselves, and primary and secondary schools in the form of teaching materials. While in nonformal institutions, the study of religious sciences has accommodated the students to be moderate in life in society. This harmony facilitates the inclusion of religious moderation in all walks of life.